The reality of financial inclusion in light of economic transformations evaluating: experiences from Arab Countries (Saudi Arabia, Egypt, Algeria) - Lakhdar, Ayachi; Dalal, Belghit (The International tax journal, 2025)
This research aims to evaluate the financial inclusion experiences in Arab countries, with a focus on the impact of recent economic transformations in these nations. It highlights how economic and social transformations, such as digitization and the increased use of financial technology, affect individuals' access to formal financial services in the Arab world. The study also addresses the challenges facing financial inclusion, including poverty, financial illiteracy, and social inequality, and explores how these factors influence individuals' ability to benefit from these services. The study concentrated on three key case studies: Saudi Arabia, Egypt, and Algeria. The research yielded several important findings. First, the results confirmed a significant improvement in financial inclusion in all three countries, where both Saudi Arabia and Egypt adopted innovative digital financial policies that enhanced access to financial services, particularly through digital platforms and electronic wallets. In Algeria, the digital transformation led to an increase in the use of electronic payment services and mobile money transfers, although financial inclusion remains limited when compared to global standards. Second, the study demonstrated that technical and regulatory challenges, such as the lack of digital infrastructure in rural areas, continue to pose barriers to achieving comprehensive financial inclusion.